Difference Strategy and Innovation in Competitive Advantage to Increasing Sales in Godho Batik Banyuwangi - Elok Rosyidah (UPT Penerbitan Universitas Jember, 2021)
Various batik industries are emerging and display different competitive advantages, ranging from motifs, raw materials, production processes, marketing strategies and various elements that support them. Godho Batik is increasingly recognized by the wider community through its characteristics. Various achievements, product quality and new product innovations and implemented marketing resulted in an increase in sales at Godho Batik. Innovation can be one of the factors in order to survive in the market by providing value over other batik industries. Sales of an industry above the average of other competitors can be owned if through competitive advantage. This study aims to analyze the strategy of differentiation and innovation in competitive advantage to increase sales of Godho Batik products. This research uses a descriptive qualitative approach. Data were collected through observation, interview and documentation techniques. The results show that image and product are the focus of differentiation strategy in this study, while product innovation and marketing innovation are the focus of innovation in this study. Differentiation and innovation strategies in an effort to increase sales of Godho Batik can be proven from sales turnover data which continues to increase from year to year and can maintain itself in a competitive market position. Keywords: Competitive advantage, differentiation strategy, product innovation